A Study on Psychological Capital Improvement Using Experiential Learning Model- The Catholic University of Taiwan As an Example - Chun Yao Tsai; Wen Hsiang Lai; Ying Chyi Chou3 (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
The purpose of this research is to improve the Psychological Capital of Catholic University students by Using Experiential Learning Model. This study was given a total of 300 questionnaires randomly sampled by 1,200 students from 25 classes of Catholic University in Taiwan, Republic of China. There are 53.4% students believe that I have the ability to become a student with a balanced five educations, show that Strongly Agree & Agree Percentage of “Self- efficacy” is relatively low. But when through Kolb’s Experiential Learning Model as Concrete Experience (CE), Reflective Observation (RO), Abstract Conceptualization (AC), and Active Experimentation (AE) to group practice, complete a charity task. There are 81.2% students facing the task, I will imagine ways to achieve the goal, show that Strongly Agree & Agree Percentage of “Hope” is relatively high. Therefore, this research is to improve the Psychological Capital of Catholic University students by Using Experiential Learning Model. At the same time also encourage students to pursue an education that combines excellent humanities, cultural development and professional services.